A Critical Analysis of Bent-rib Metaphor Ḥadith: Embracing Women's Uniqueness and Empowerment - Nurul Jannah Zainan Nazri; Mohd Arif Nazri; Nurul Mukminah Zainan Nazri (IIUM Press, 2024)
Non-Indexed Publication